Phenotypic and molecular characterization of extended-spectrum beta-lactamase-producing Escherichia coli in Bangladesh. - Taslima T Lina (Public Library of Science (PLoS), 2014)
Background Resistance to cephalosporins in Enterobacteriaceae is mainly due to the production of extended-spectrum beta-lactamase (ESBL). Little is known about ESBL-producing bacteria in Bangladesh. Therefore, the study presents results of phenotypic and molecular characterization of ESBL-producing Escherichia coli from hospitals in Bangladesh. Methods A total of 339 E. coli isolated from patients with urinary tract and wound infections attending three different medical hospitals in urban and rural areas of Bangladesh between 2003-2007 were screened for ESBL-production by the double disk diffusion test. Isolates with ESBL-phenotype were further characterized by antibiotic susceptibility testing, PCR and sequencing of different β-lactamase and virulence genes, serotyping, and XbaI-macrorestriction followed by pulsed-field gel electrophoresis (PFGE). Results We identified 40 E. coli with ESBL phenotype. These isolates were resistant to ceftriaxone, ceftazidime, cefotaxime, aztreonam, cefepime, and nalidixic acid but remained susceptible to imipenem. All but one isolate were additionally resistant to ciprofloxacin, and 3 isolates were resistant to cefoxitin. ESBL genes of blaCTX-M-1-group were detected in all isolates; blaTEM-type and blaOXA-1-type genes were detected in 33 (82.5%) and 19 (47.5%) isolates, respectively. Virulence genes that are present in diarrhoeagenic E. coli were not found. Class-1 integron was present in 20 (50%) isolates. All the ESBL-producing E. coli isolates harbored plasmids ranging between 1.1 and 120 MDa. PFGE-typing revealed 26 different pulsotypes, but identical pulsotype showed 6 isolates of serotype O25:H4. Conclusion The prevalence of multidrug-resistant ESBL-producing E. coli isolates appears to be high and the majority of the isolates were positive for blaCTX-M. Although there was genetic heterogeneity among isolates, presence of a cluster of isolates belonging to serotype O25:H4 indicates dissemination of the pandemic uropathogenic E. coli clone in Bangladesh.